Is Deterioration of Surface Properties of Resin Composites Affected by Filler Size? - H. Elbishari; N. Silikas; J. D. Satterthwaite (Hindawi Limited, 2020)
Statement of the problem. Resin composite restorations can lose their aesthetic properties in clinical service. Purpose. To investigate the effect of filler size on surface gloss and roughness of resin composites using a glossmeter and 3D noncontact surface topography, respectively, before and after tooth-brushing abrasion. Materials and Methods. Seven model resin composites and one commercial were tested in the study. All materials were first polished, and then the surface gloss and 2D and 3D roughness parameters were recorded. Materials are then subjected to abrasion in a tooth-brushing simulator. Roughness parameters were recorded after 10,000 cycles, and after 20,000 cycles, both roughness and gloss were recorded. One-way ANOVA and Bonferroni post hoc test (p<0.05) were used to analyze data. Conclusion. Filler size is strongly correlated to gloss and surface roughness retention.